Success of immediate loading implants compared to conventionally‐loaded implants: a literature review. Issue 3 (15th May 2015) - Al‐Sawai, Abdul‐Aziz; Labib, Hussein
Abstract: The purpose of this systematic literature review was to compare the clinical performance between conventionally‐ (delayed) and immediately‐loaded implants. A literature search of studies published between 1995 and 2012 was performed using several electronic databases and the following key words: "immediate loading", "dental implants", "immediate function", "early loading", "oral implants", "immediate restoration", and "systematic review" was performed. The electronic search was supplemented with hand‐searching in dental journals and cross‐referencing within the selected articles. Studies were considered for inclusion if they analyzed the success of the immediate loading protocol for implants, with emphasis given to randomized, controlled clinical trials. Among the clinical studies extracted from the literature, 120 studies met the inclusion criteria and were included in this systematic review. These studies included trials that involved yielded consistent results of success rates of immediately‐loaded implants comparable to those known from conventionally‐loaded implants, which were subjected to the immediate loading protocol or other loading protocols. According to the findings, there is evidence to suggest that immediate loading protocols demonstrate high implant survival rates and could be cautiously recommended for certain clinical situations. However, studies with a high level of evidence, especially randomized, controlled trials, performed over a longer timeframe are required to show a clear benefit over conventional and other loading types.